Two new species of Paramphiascella Lang (Copepoda: Harpacticoida: Miraciidae) from a brackish water pond in Thailand - Chullasorn, Supawadee (Zootaxa, 2010)
Two new species of the harpacticoid genus Paramphiascella Lang, 1944 were collected from a brackish water pond located at the Coastal Fisheries Research Development Center, Department of Fisheries, Samut Sakhon province, Thailand, and are described herein. Paramphiascella dahmsi sp. nov. and P. ferrarii sp. nov. are similar to other species of the genus in having a cylindrical body shape, eight-segmented antennules, and both the baseoendopod and exopod of the female P5 with five setae. However, the two new species can be distinguished from other congeners by having one big ovate-striated knob at the inner edge of the male P1 basis. Paramphiascella dahmsi bears in addition two ovatestriated knobs on the anterior surface of the proximal rim of the male P1 Enp1 while P. ferrarii is without any knobs on the endopod. The Enp2 of male P2 of P. dahmsi is distally attenuated, with a medially pointed knob close to Enp1. Adjacent to the knob there are two setae, one spinulose and one pectinate, and one club-like seta bifurcate at its tip. In P. ferrarii, the medial knob is rounded, a second long attenuation arises near the base of two unequal spinulose setae and the club-like seta is absent. In addition, the P2 Enp1 bears an inner spinulose seta in P. dahmsi, while in P. ferrarii it bears a pectinate seta. These characters are suggested as autapomorphies of the new species.